PCL/chloramphenicol/hexafluoro-2-propanol solution for fabrication of various bioactive drug delivery materials; Перспективы развития фундаментальных наук; Т. 2 : Химия - Volokhova A. A. Apollinariya Aleksandrovna (2021, 2021)
Заглавие с экрана